„Auf den Hochstraßen des Weltwirtschaftsverkehrs“.: Zur europäischen Ideologie der „Erschließung“ im ausgehenden 19. und frühen 20. Jahrhundert - van Laak, Dirk (Comparativ, 2009)
Several generations of geopolitically influenced experts were overwhelmed by the infrastructural achievements of the late 19th century. The whole world appeared to be partitioned into spheres of influence by means of technology. The power of opening up and developing foreign territories seemed to demonstrate a superior historical position of the ‘white race’. The Europeans felt reconfirmed in assuming the prevailing position being entitled to the principles of efficiency. Consequently the indigenous people as antipodes were often described in terms of laziness or with the need to be awakened to productive labour. However, the ideology of ‘development’, understood as a ‘civilizing mission’ that was based in an almost religious belief in the supremacy of European technology, did not merely spark competition among the colonial countries, its advancement also contributed to the imagination of a possible European ‘decline’ in the future. This article seeks to assess the ‘technocratic approach’ within the history of globalisation and its interrelation to images of European ‘progressive technology’ as mirrored in the colonial ‘other’.